2005
DOI: 10.2174/1389201054553671
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Consequences of Weightlessness Promote Advances in Clinical and Trauma Care

Abstract: Cardiovascular adaptations driven by exposure to weightlessness cause some astronauts to experience orthostatic intolerance upon return to Earth. Maladaptations of spaceflight that lead to hemodynamic instability are temporary, and therefore astronauts provide for researchers a powerful model to study cardiovascular dysfunction in terrestrial patients. Orthostatic intolerance in astronauts is linked to changes in the autonomic control of cardiovascular function, and so patients that suffer neurocardiogenic syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 82 publications
0
7
0
4
Order By: Relevance
“…Researchers at the USAISR and others have pioneered the use of LBNP as a model to study the effects of hypovolemia in conscious humans 17,30,31. Previous studies have shown that changes in hemodynamics and autonomic responses produced by sequential LBNP are comparable to hemorrhage produced in large animals or mild to moderate blood removal in humans 17,30–33. While the model produces changes in CO and MAP that appear to be similar to actual clinical hemorrhage, there is still much to be explored regarding the physiologic mechanisms of microvascular perfusion and tissue oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers at the USAISR and others have pioneered the use of LBNP as a model to study the effects of hypovolemia in conscious humans 17,30,31. Previous studies have shown that changes in hemodynamics and autonomic responses produced by sequential LBNP are comparable to hemorrhage produced in large animals or mild to moderate blood removal in humans 17,30–33. While the model produces changes in CO and MAP that appear to be similar to actual clinical hemorrhage, there is still much to be explored regarding the physiologic mechanisms of microvascular perfusion and tissue oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, during spaceflight, gravity-generated forces are absent and the mechanical stimulation of tissues is greatly diminished. Direct and immediate physiological responses to microgravity-induced mechanical unloading include adaptive losses of bone [1], [2], [3], [4], [5], [6] and muscle mass [7], [8], [9], [10], and alterations in cardiovascular function [11], [12], [13], [14]. Because of practical reasons, most space biological animal research has focused on the short-term effects of spaceflight, and thus our understanding of long-term effects of microgravity exposure is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Microgravity leads to bone loss (153). Like ionizing radiation, it alters physiological functions (60,265) and contributes to oxidative stress (153). Interestingly, analyses of urinary excretion before, during, and after long-duration space flight (4-9 months) on the Russian space station MIR and short-duration missions on the shuttle revealed opposite results in-flight and post-flight.…”
Section: Gravitational Changes In Space and Oxidative Stressmentioning
confidence: 99%